Scaling Up of Liquid Soap Production from Recycled Frying Oil - Wijana, Susinggih; Purnomo, Dodyk; Taslimah, M. Y. (Fakultas Teknologi Pertanian Universitas Brawijaya, 2010)
The aim of this study was to know the effect of the increasing volume in saponification process on the 88 l reactor on the soap quality and efficiency of the process. The experiment consisted of 2 sub-experiments. The first sub-experiment was the factorial experiment with 2 factors, the time of stirring (60, 90 and 120 minutes) and the ratio of water to soap (2:1; 3:1, and 4:1 w/w). The second sub-experiment was scaling up with mixed material volume of 5, 15 and 25 liters. Â The effectiveness index showed that the best soap quality for laboratory scale obtained at 90 minutes stirring time and ratio of water to soap of 2:1 (w/w). Â Meanwhile, scaling up showed that the increasing volume tended to decrease the quality of the product, although it still met the industrial standard of liquid soap.Keywords: scaling up, recycled frying oil, liquid soap